Enhancing environmental sustainability and operational efficiency in a case study of limestone quarry in an arid climate - Hussein A. Saleem; Abebe Temesgen Ayalew (Scientific Reports)
Abstract This study explored innovative approaches to enhance environmental sustainability and operational efficiency in quarry operations in Ethiopia, focusing on the limestone quarry of the National Cement Factory. This open-air quarry, dedicated to produce gravel and aggregate for construction materials, presented significant environmental challenges, including air pollution, dust emissions, and noise pollution. The study examined the integration of automated environmental monitoring systems, dust and noise control techniques, and sustainable site rehabilitation. Automated environmental monitoring systems, incorporating IoT sensors and machine-learning algorithms, provide real-time data on air quality, dust levels, and noise pollution. This data-driven approach enables predictive analytics for early hazard detection and proactive mitigation. In parallel, eco-friendly practices such as non-toxic dust suppressants and sustainable land reclamation strategies mitigate the ecological impacts of quarrying. These strategies, tailored to arid environments, include the use of indigenous plant species to restore biodiversity and prevent soil erosion. This study employs a case study methodology, collecting and analyzing real-time data before and after interventions. The findings demonstrate significant improvements, including a 45% reduction in dust levels, a 15% reduction in noise levels, and a 266% increase in vegetation cover. Additionally, the results highlighted the role of local regulations, industry collaboration, and workforce training in achieving sustainable quarrying operations. The proposed approach enhanced environmental compliance, safety, and operational efficiency, offering a model for similar quarrying sites in arid climates.